A new species of Lycaena Fabricius, 1807 (Lepidoptera, Lycaenidae) from Mongolia with a review of genitalia characters of the related taxa - Churkin, Sergei V.; Kolesnichenko, Kirill K. (Zootaxa, 2019)
Lycaena ratushinskayae sp. n. is described from the Baitag mountain range isolated in the Dzhungarian Gobi desert, SW Mongolia. Externally the new species strongly differs from related taxa by a dark-gray underside and deep reddish upperside with widened blackish margins. A new study of the male genitalia is performed with the diagnosis of new and all related species. It is confirmed that juxta presents the most valuable sclerite for taxonomic purposes.